2020
DOI: 10.1163/15685357-20203001
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Religion for the Evaluation of Everyday Ecological Decisions by German Adolescents

Abstract: Although previous research has addressed the relationship between religion and ecology in a variety of ways, little is known concerning how religious orientation affects concrete everyday ecological decisions, although these are centrally important for environmental education. Being interested in elucidating the preconditions of ecological learning in Biology and Religious Education in schools, the authors have developed an approach based on maximum concretion with regard to the ecological decision in which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…For example, it can support religiously oriented students to develop an attitude of religious stewardship, but non-religious students are also amenable to this orientation. This and other studies have shown that questions of sustainable development and climate change are increasingly perceived as religious or spiritual issues-even beyond explicit religious orientations (Altmeyer and Dreesmann 2020b;Jenkins et al 2018;Berry 2013;Sponsel 2012;Gottlieb 2006). Because of this, religious education could raise the question "how our ecological and moral imaginations might be stimulated through an encounter with these alternative [i.e.…”
Section: Discussionmentioning
confidence: 78%
“…For example, it can support religiously oriented students to develop an attitude of religious stewardship, but non-religious students are also amenable to this orientation. This and other studies have shown that questions of sustainable development and climate change are increasingly perceived as religious or spiritual issues-even beyond explicit religious orientations (Altmeyer and Dreesmann 2020b;Jenkins et al 2018;Berry 2013;Sponsel 2012;Gottlieb 2006). Because of this, religious education could raise the question "how our ecological and moral imaginations might be stimulated through an encounter with these alternative [i.e.…”
Section: Discussionmentioning
confidence: 78%
“…Das gilt zum einen für die von ihr thematisierten Glaubensinhalte. Die ökologische Situation führt zu neuen Fragen der Kinder und Jugendlichen nach Sinn, Ordnung und Hoffnung, die religiös offen sind (Altmeyer & Dreesmann, 2020). Die überkommenen religiösen Antworten auf diese Fragen können von der Krise nicht unberührt bleiben: Was bedeutet es für Gottebenbildlichkeit als Freiheit, wenn die Sünde ins Unermessliche wächst, da die drohende Apokalypse selbst zu verantworten ist?…”
Section: Die öKologische Krise Als Herausforderung Für Religiöse Bildung: Skizze Rbneunclassified